Comprehensive analysis of chromatin states in atypical teratoid/rhabdoid tumor identifies diverging roles for SWI/SNF and polycomb in gene regulation - Erkek, Serap; Johann, Pascal-David; Zapatka, Marc; Sturm, Dominik; Jones, David T. W.; Korshunov, Andrey; Wolf, Stephan; Mallm, Jan-Philipp; Witt, Olaf; Kulozik, Andreas; Korbel, Jan Oliver; Lichter, Peter; et al. (Cancer cell, 2019)
Summary - Biallelic inactivation of SMARCB1, encoding a member of the SWI/SNF chromatin remodeling complex, is the hallmark genetic aberration of atypical teratoid rhabdoid tumors (ATRT). Here, we report how loss of SMARCB1 affects the epigenome in these tumors. Using chromatin immunoprecipitation sequencing (ChIP-seq) on primary tumors for a series of active and repressive histone marks, we identified the chromatin states differentially represented in ATRTs compared with other brain tumors and non-neoplastic brain. Re-expression of SMARCB1 in ATRT cell lines enabled confirmation of our genome-wide findings for the chromatin states. Additional generation of ChIP-seq data for SWI/SNF and Polycomb group proteins and the transcriptional repressor protein REST determined differential dependencies of SWI/SNF and Polycomb complexes in regulation of diverse gene sets in ATRTs.
Available online 27 December 2018
Gesehen am 08.05.2019